PENGARUH PEMBERIAN HERBAL SPRAY BERBASIS BIOAKTIF DARI SPIRULINA (Spirulina sp.) TERHADAP EKSPRESI iNOS PADA SEL β-PANKREAS DAN AKTIVITAS PROTEASE PADA LUKA TIKUS DM TIPE 1 - Mahdi, Chanif; Agustin, Rachmawati Dwi; Aulanni'am, Aulanni'am (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
Diabetes mellitus (DM) is a disease caused by disorders of carbohydrate metabolism. DM can also be caused by the destruction of β cells of the islet of Langerhans in the pancreas that functions as an insulin-producing. In patients with DM when injured will be more difficult in the wound healing process. This study aims to determine the effect of Spirulina herbal spray against changes cuts, reduction in iNOS expression in β-cells of the pancreas and protease activity in wound induction results MLD STZ rats (Multi Low Dose Streptozotocin) at a dose of 20 mg / kg for 5 consecutive days in a row. In this study using rats (Rattus norvegicus) were divided into three groups with each group consisting of 5 rats, the three groups are groups of healthy mice with skin wound on his back, a group of diabetic rats with wound and groups diabetic rats with wound and to get therapy of Spirulina herbal spray during 14 days. The results showed that administration of Spirulina herbal spray can reduce the length of incision wounds in diabetic rats from 4,28 cm until 0,5 cm, able to decrease the expression of iNOS in pancreatic β-cells of DM type 1 rats and also able to decrease of 48,23% protease activity in wound DM type 1 rats.Keywords: protease activity, DM type 1, iNOS expression, herbal spray Spirulina, wound.